Quelle place le Cadre européen commun de référence pour les langues accorde-t-il aux variations diatopique, diastratique et diaphasique? - Perko, Gregor (Vestnik za tuje jezike, 2009)
This paper proposes a critical analysis of the treatment of the diaphasical, diatopical and diastratical variation in the Common European Framework of Reference for Languages as well as in some instruments and manuals based on this reference document, namely in reference descriptions for French and in handbooks intended for foreigners preparing for the DELF/DALF examinations.
Keywords: francoščina; French; jezikovne variante; diafazična zvrstnost; diatopična zvrstnost; distratična zvrstnost; učenje tujih jezikov; skupni evropski okviri